Prevention Communication Approach to COVID-19 Virus at the Bantul Regency Mosque - Nurjanah, Adhianty (Jurnal Ilmu Komunikasi, 2023)
The communication approach is crucial in facing the pandemic as a preventive measure and reducing therisk of its spread. COVID-19 prevention should be studied to reduce the risk of transmission. The highestincrease occurred in the Special Region of Yogyakarta, particularly in Bantul Regency, one of the reasonsis the activity of visiting places of worship that do not comply with health protocols. The aim of theresearch was to examine the preventive communication actors for the transmission of COVID-19 at the Al-Muharram Mosque, Bantul Regency. The research method used is qualitative with a case study approach.The research found that the preventive communication actors of COVID-19 are always conveyed by theTakmir of Al-Muharram Mosque, either directly during Friday Khutbah, Pengajian, or through socializationvia banners, posters, and social media such as Instagram, Facebook, and personal Whatsapp of the Takmir ofthe Mosque to provide warnings and prevention of the spread of the COVID-19 virus. The communicationcontent conveyed by the Takmir of the Mosque includes topics related to hadiths in facing an epidemic,implementing health protocols, and encouraging early detection culture for each individual’s health to preventCOVID-19 transmission. The role of the trusted Takmir supported by appropriate data sources and mediabecomes an effective communication approach shown by the orderly behavior of the congregation and thecommunity. The contribution of this research found that religious figures have a role in handling COVID-19through persuasive and educational messages conveyed in sermons and arranged as religious messages.